An electro-responsive imprinted biosensor with switchable affinity toward proteins. Issue 66 (31st July 2018) - Wei, Yubo; Zeng, Qiang; Huang, Jianzhi; Hu, Qiong; Guo, Xinrong; Wang, Lishi
Abstract : We combined electro-responsive materials with molecular imprinted polymers (MIPs) to develop an electro-responsive imprinted biosensor for the first time. Abstract : We combined electro-responsive materials with molecular imprinted polymers (MIPs) to develop an electro-responsive imprinted biosensor for the first time. As an electric field controlled gate, the biosensor exhibits a novel self-cleaning ability, as well as switchable affinity toward proteins in aqueous media, based on a reversible structure change.